Developing nurse leaders across the Americas: evaluation of an online nursing leadership course - Johis Ortega; Mary Hooshmand; Cynthia Foronda; Maria Padron; Desiree Simon; Michelle Waters; Silvia Cassiani; Nilda Peragallo Montano (Pan American Health Organization, 2018)
Development of leadership capacities in the nursing workforce is essential to achieving universal health in the Region of the Americas. This evaluation considered the effectiveness of an online leadership course offered in English and Spanish to nurses throughout Latin America and the Caribbean. The online course was an asynchronous eight-module leadership nursing course created and offered by the Pan American Health Organization (PAHO) Virtual Campus. A retrospective, descriptive design was used to evaluate learner performance data from the modules. Learner performance on the course was analyzed. Electronic surveys were distributed to individuals who withdrew prior to course completion to obtain information regarding the reason for withdrawal. In all, 289 individuals from 41 countries participated in the online course. Learner performance demonstrated improvement from pre- to post-test. The most frequent reason for not completing the course was being too busy with other obligations. The Spanish-language course version received more enrollment applications than any other course in the virtual campus' 12-year history. The evaluation concluded that continuing education that develops nursing leadership is desired across Latin America and the Caribbean. Online education through the PAHO Virtual Campus may be a low-cost yet powerful means of disseminating knowledge to the nursing workforce throughout the Americas.